PENDIDIKAN KELUARGA MENURUT SYAIKH NAWAWI DALAM KITAB UQÛD AL-LUJJAYN FÎ BAYÂNI HUQÛQ AL-ZAWJAIN - Muqoffi Muqoffi; Masykurotus Syarifah (LP2M IAI Miftahul Ulum Pamekasan, 2020)
Nowadays the tempest of the household not only raises acute disharmony between husband and wife but also has fatal consequences for the moral decadence of children. Therefore, it is felt necessary to examine family education in the book of Uqûd al-Lujjayn by Shaykh Nawawi to transmit objective steps in maintaining the stability of Islamic households to the community. This research is a type of literature study using a qualitative approach. From the results of the study, it was found that the purpose of family education is to care for the family from Hellfire with the approach of the science of jurisprudence and morals. Educators are fathers and mothers, while students are wives and children through the methods of instruction and habituation, question and answer, punishment and exemplary. The internalization of Shaykh Nawawi's family education is very relevant in modern families as a preventive measure from the threat of materialistic life style threats. Among them, optimizing the husband in playing his role as an educator for children and wife towards the inculcation of sharia values ​​and character education, not just fulfilling birth obligations. Likewise a mother establishes herself as a domestic worker and child educator. An ideal formulation of family education in realizing the quality of faith and piety not the quantity of thrones and possessions. But the concept of Shaykh Nawawi in intimidating children in giving orders needs to be synergized with typical modern children. For children who are hard-hearted, arrogant and egocentric, this concept is considered not accurate, so the relevance is not right. Likewise, direct punishment to children and wives is considered less relevant. Imposing punishment must be carried out procedurally with the principle of proportional and conditional sourced from the principle of min al-akhaffi ilâ al-asyad: starting from the lightest to the heaviest.